PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT SISA JAMUR UNTUK MENINGKATKAN PERTUMBUHAN BIBIT TEBU (Saccharum officinarum L.) DI TANAH GAMBUT - Sawaludin; Nurhayati; Sarwendah Ratnawati Hermanto; Rosmalinda; Beny Setiawan (Journal of Agro Plantation (JAP), 2022)
Sugarcane (Saccharum officinarum L.) is an important commodity as the main ingredient for sugar production. Good sugarcane growth will produce high sugar yields so that sugar production also increases. Seed maintenance is one of the important stages in preparing good plants, especially fertilization. Oil palm empty fruit bunches residual mushroom (TKSJ) are one of the solid wastes produced from processing palm oil mills and can be used as an organic fertilizer. The purpose of this study was to determine the effects of giving TKSJ on the growth of sugarcane seedlings in peat soil media. This study used a completely randomized design (CRD) consisting of 5 treatments and 5 replications, namely without TKSJ compost (K0); TKSJ 25% (K1); TKSJ 50% (K2); TKSJ 75% (K3) and TKSJ 100% (K4). Observation parameters consisted of leaf length (cm) and root wet weight (g). The data were analyzed by Analysis of Variance (ANOVA). If it has a significant effect, then it is continued with Duncan's Multiple Range Test (DMRT) at a level of 5%. The results showed that composting